Health-Related Quality of Life for Chronically Ill Children. Issue 1 (January 2015) - Cantrell, Mary Ann; Kelly, Michelle M.
<x xml:space="preserve">Abstract</x> Abstract Approximately 43% of children in the United States (32 million) are currently living with at least 1 of 20 common chronic childhood illnesses. The most common chronic childhood illnesses are asthma, cystic fibrosis, diabetes, obesity, malnutrition, developmental disabilities, cerebral palsy, consequences of low birthweight, and mental illness. For all chronically ill pediatric populations, the outcome of health-related quality of life (HRQOL) is particularly important because many of these children have not and will not be cured, and will continue to manage their chronic illness into adulthood. Advances in biomedical science and technology continue to improve efficacy of treatments and care for chronically ill children, adolescents, and their families, which highlight the importance measurement of HRQOL as a treatment and health status outcome. The construct of HRQOL is subjective, multidimensional, dynamic, and unique to each individual. It includes aspects of physical, psychological, social function, and goal attainment. Outcomes of HRQOL now include the financial implications for these children and their families, as well as financial and organizational consequences for healthcare planning and delivery of services. This article reviews the importance of HRQOL as a health outcome for chronically ill children. A historical overview and synthesis of the conceptualization and measurement of HRQOL for the chronically ill pediatric population is provided. Current research investigations that have measured health outcomes using individual scales tailored to children's specific symptoms health outcomes, such as PROMIS®—Patient Reported Outcomes Measurement Information System—are reviewed. The clinical applications of HRQOL outcomes research include facilitation of patient-healthcare provider communication, improved patient satisfaction, identification of hidden morbidities, a positive impact on clinical decision making, and improvement of patient outcomes over time.